Growth dynamics of selective-area-grown rutile-type SnO2 on TiO2 (110) substrate. (1st April 2023) - Takane, Hitoshi; Oshima, Takayoshi; Tanaka, Katsuhisa; Kaneko, Kentaro
Abstract: We demonstrated selective-area growth of r-SnO2 on a SiO2 -masked r-TiO2 (110) substrate. The heteroepitaxy on a window started with a Volmer–Weber mode to grow islands with 100-, 11̄0-, and 011-faceted sidewalls, whose growth shapes were consistent with the rutile structure's equilibrium shape. The islands coalesced each other to make a flat (110) top surface on a striped window, and lateral overgrowth started after the complete coverage of the window. Cross-sectional transmission-electron-microscopy observation of the stripe revealed that misfit dislocations propagated perpendicularly to the facet planes by the image force effect and that the dislocation density reduced substantially in the wing regions.